Mandatory COVID-19 vaccination in human rights and utilitarianism perspectives - Zaid Zaid; Wempy Setyabudi Hernowo; Nanik Prasetyoningsih (International Journal of Public Health Science (IJPHS), 2022)
Departing from the mandatory vaccination had been debated and received a lot of rejection which has caused intense emotions. In this study, the authors tried to evaluate the mandatory regulation of coronavirus disease 2019 (COVID-19) vaccination from a human rights and utilitarianism perspective. By conducting normative research method, this study revealed that indeed the obligation that tends to be coercive for COVID-19 vaccination seems to violate individual human rights which each individual has the right to decide for themselves whether they want to participate in the program or not without coercion. However, mandatory vaccination is still justified, from a human rights perspective, to protect other people's rights not to be infected with infectious diseases. This is also in line with a utilitarian perspective that departs from the argument that vaccines provide a myriad of benefits for many people in the midst of a pandemic, therefore to create benefits for the majority of society, the mandatory COVID-19 vaccination is something that is needed. Even if necessary, both sanctions and punishments can be justified in utilitarianism to achieve the greatest utility for the society.